Photography by Hermelind Le Doeuff | Linguistic fieldwork in South Africa|Power (7/12) - (:unkn) unknown (My University, 2022)
This photograph has been captured by Hermelind Le Doeuff during a sociolinguistic fielwork conducted in the Eastern Cape region of South Africa in 2022. This fieldwork aimed at documenting contemporary discourses, representations and attitudes with regard to the sociolinguistic practices of ukuhlonipha/isihlonipho among Xhosa speakers.
Keywords: African Research